Evaluation of body composition as a potential biomarker in spinal muscular atrophy. Issue 4 (7th February 2020) - Baranello, Giovanni; De Amicis, Ramona; Arnoldi, Maria Teresa; Zanin, Riccardo; Mastella, Chiara; Masson, Riccardo; Leone, Alessandro; Alberti, Katia; Foppiani, Andrea; Battezzati, Alberto; Bertoli, Simona
Abstract: Introduction: We aimed to investigate the correlation between body composition (BC) and spinal muscular atrophy (SMA)‐specific motor function assessments. Methods: Patients with SMA types I or II, aged 1 to 10 years, were recruited in this cross‐sectional study. The protocol included anthropometric measurements, and dual‐energy X‐ray absoprtiometry to assess fat mass (FM), lean mass (LM), fat‐free mass (FFM), FM and FFM indexes (FMI, FFMI), and motor function assessments (Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders scale for SMAI, and Hammersmith Functional Motor Scale―Expanded for SMAII). Results: Eighty‐eight children were included. All had a higher FM percentage than reference values. Motor function was moderately correlated with body mass index (BMI), FFMI, and LMI in SMAI, and weakly correlated with FFMI, LMI, and LM:FM ratio in SMAII. Discussion: BC shows promise as a potential biomarker for SMA, but further studies are needed.